Baking Reflections with 3D Gaussian Splatting in Real Time Ray-Tracing Rendering - Lenk, Alan; Antunes, Anselmo; Macêdo, Horácio; Clua, Esteban (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2025: Anais da XXXVIII Conference on Graphics, Patterns and Images, 2025)
This paper presents a method for rendering static reflections using precomputed 3D Gaussian Splatting (3DGS) models, aiming to enhance conventional rendering pipelines with realistic and efficient reflections. Unlike traditional techniques such Environment Mapping, which suffer from occlusion limitations and static viewpoint assumptions, our approach decouples reflection generation from the main rendering process by sampling color and radiance from 3DGS models organized in an octree structure. By constraining the number of Gaussians per node, our method allows for scalable control over quality and performance, achieving real-time frame rates in several synthetic and real-world scenarios. We show that even with simplified models, the reflections remain visually plausible, particularly in scenes with diffuse materials. Our results demonstrate accurate parallax and off-camera content reproduction, with potential applications in games, mixed reality, and offline rendering.